Idiomatic Expressions Found in Taylor Swift’s Song “Shake It Off” Lyrics - Tsulis Khoerunnisa Amanah; Otong Setiawan Djauhari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The present study aims to identify and analyse idiomatic expressions in the lyrics of